New standards in weight management: recent and future drugs for the treatment of obesity - Van Gaal, Luc (Henry Stewart Talks, 2007)
Pharmacotherapy as target for 5 to 10 % weight loss option, Pharmacotherapy as an additional approach for weight management programs, Characteristics of appropriate anti-obesity agents, Actual experience with anti-obesity agents, Potential new agents for the future, Metabolic "beyond weight loss" effects, Safety
Archived at 2021/02/25